First report of Bacillus spp. entomopathogenic to Melanaphis sacchari Zehntner (Hemiptera: Aphididae) - Toledo-Hernández, Erubiel; Olivera-Cruz, Stazie Kimberly; Toribio Jiménez, Jeiry; Romero-Ramírez, Yanet; Lormendez, Caleb C.; Peña-Chora, Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2021)
Due to the lack of knowledge of pathogenic bacteria to Melanaphis sacchari, the objective of this work was to evaluate the pathogenicity of bacterial strains against this aphid. In vitro bioassays were carried out at the Autonomous University of Guerrero in 2019. By intake in a contaminated diet, four strains were evaluated in two treatments of 10 and 100 μg ml-1 of total protein. Bioassays showed that the strains were pathogenic to the aphid, resulting in mortality at 48 h of between 35 ±8% to 63 ±12% at a concentration of 10 μg ml-1. While, at a concentration of 100 μg ml mortality was around 48 ±4% to 90 ±7%. The most virulent strains against the aphid at a concentration of 10 μg ml-1 were ETH-109 and ETH-117, resulting in mortality of 58 ±8% and 63 ±12%, respectively. Whereas, to the concentration of 100 μg ml-1 the most virulent strain was ETH-109 causing mortality of 90 ±7%, followed by the ETH-117 strain with 73 ±5% of dead aphids.
Keywords: bacteria; entomopathogenic; plague; sorghum